Produção de biossurfactantes por bactérias isoladas de solo de meloeiro - Nogueira, Kamila Pátila de Morais (Universidade Federal Rural do Semi-Árido, 2019)
Biosurfactants are molecules synthesized by microorganisms of amphiphilic structure composed of a hydrophilic region and another hydrophobic region. This characteristic allows these molecules to be able to exist and interact in the middle of two immiscible phases, and act by reducing the surface and interfacial tension of these systems, besides forming emulsions. Some bacteria and fungi are able to synthesize biosurfactant molecules, with emphasis on the genus Bacillus. When compared to chemical surfactants, because they are compounds synthesized by microorganisms, they present marked advantages such as low toxicity, high biodegradability, and efficiency in reducing surface tension. Despite this, biosurfactants present difficulties in the market, since their cost of production is higher when compared to chemical surfactants, being evident the need to find more lineages that synthesize these compounds. In this context, the present study seeks to track the production of biosurfactants by bacteria isolated from the rhizosphere of the melon soil. The study was conducted through the isolation directed to bacteria of the genus Bacillus, through thermal shock, followed by cultivation in Nutritive Agar. Submerged culture was carried out in Mineral Medium for 48h, for the synthesis of biosurfactants. For the detection of biosurfactants the oil spreading test was carried out using 0.5 g of oil deposited in 50 ml of distilled water. 200 μl of supernatant from each line was applied to the surface of the oil, and the burst halos were measured. For the detection of emulsifying activity, the emulsification index test was carried out using 2 ml of kerosene added with 2 ml of supernatant and subjected to stirring. After 24h the emulsification indices of each of the lines were obtained in order to verify the formation of emulsions. The results obtained were promising with 4 lines showing significant tensoactive activity, with halos occupying more than 50% of the plate diameter. The emulsification index also showed the ability of these lines to form emulsions, with promising results above 40% in 5 of the 8 lines. In this way the study proved to be successful, with the production of biosurfactants by the microorganisms collected.
Monografia
Keywords: Biossurfactante; Bioemulsificante; Bacillus; Lipopeptídeos; Biosurfactant; Bioemulsifier; Bacillus; Lipopeptide; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA